Comparative Study of Harmonics to Noise Ratio of Closed Organ Pipe at First and Second Resonance - Adhikari, S.K. (BMC Journal of Scientific Research, 2022)
A sound wave has two components as periodic and non-periodic whose ratio is known as harmonic to noise ratio (HNR). HNR is an important parameter to analyze the voice. It also measures the degree of hoarseness. The measure of this parameter can be done with the help of Praat software. This paper compares the HNR of a closed organ pipe at first resonance and second resonance. HNR has varied from 10.95 dB to 27.87 dB at the first resonance and 7.3 dB to 23.87 dB at the second resonance. The average values at first and second resonance are 15.69 dB and 11.99 dB respectively. From the observation table and graph, it was found that HNR is greater at first resonance than second resonance for closed organ pipe.